2018
DOI: 10.2147/opth.s171029
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral congenital nasolacrimal duct obstruction and amblyopia risk factors

Abstract: IntroductionThis study aimed to investigate the prevalence of amblyopia risk factors in patients with unilateral congenital nasolacrimal duct obstruction (CNLDO).Patients and methodsA retrospective interventional case series was performed on all consecutive patients of unilateral CNLDO who underwent probing over a 6-month period in 2017. All patients underwent a complete ocular examination, retinoscopy, axial length measurements and keratometry. Risk factors for amblyopia were noted based on the American Assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Abundant lacrimal meniscus and mucopurulent discharge which persists on the surface of the cornea may lead to blurring of vision and interferes with the clear focusing of images on the retina, which is critical for emmetropization [22]. Several authors have confirmed an increased risk for anisometropia and amblyopia in patients with CNLDO (especially long-term untreated obstructions) [22][23][24][25]. However, the effect of long-term epiphora on visual development in children is debatable and some studies reported no significant differences between children with CNLDO and general population [17,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Abundant lacrimal meniscus and mucopurulent discharge which persists on the surface of the cornea may lead to blurring of vision and interferes with the clear focusing of images on the retina, which is critical for emmetropization [22]. Several authors have confirmed an increased risk for anisometropia and amblyopia in patients with CNLDO (especially long-term untreated obstructions) [22][23][24][25]. However, the effect of long-term epiphora on visual development in children is debatable and some studies reported no significant differences between children with CNLDO and general population [17,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…A könnyelvezetés zavara nemcsak állandó diszkomfortérzést okoz a páciensnek, hanem látásromlást is előidézhet. Egyes tanulmányok szerint elhanyagolt vagy fel nem ismert esetben hosszú távon irreguláris astigmiához, illetve tompalátás kialakulásához vezethet a szemrésben megrekedt könny, hiszen sokszor a látásfejlődés legérzékenyebb időszakában változtathatja meg a fénytörést a magas könnytócsa [3][4][5][6][7]. Mások azonban megkérdőjelezik az epiphora okozta deprivatiós amblyopia kialakulásának lehetőségét, mivel a korban megfelelő átlagpopulációhoz képest a könnyező páciensek között nem találtak nagyobb arányban tompalátókat [8,9].…”
unclassified